Policy Challenges of Population Aging in Ireland - Iakova, Dora (IMF Working Papers; Working Paper, 2007)
The projected rise in age-related government spending as a share of GDP in Ireland over the next forty years is among the highest in the euro area. In the absence of reforms, public debt will increase to unsustainable levels. This paper uses the IMF's Global Fiscal Model to compare the macroeconomic effects of different fiscal strategies to accommodate the rise in age-related spending. The simulations suggest that adopting a package of measures, including an increase in the retirement age, broadening the tax base, and raising indirect taxes, would be a more growth-friendly strategy than relying exclusively on raising the social security contribution rate.